Evaluation of the in vitro growth of perolera pineapple (Ananas comosus) explants using organogenesis technique - Christian Andrei Chacin Zambrano; Yessica Paola Quintero Avila; Leydy Gabriela Rodríguez González; Johanna Alexandr Gómez Santos (Revista Colombiana de Investigaciones Agroindustriales, 2021)
From an economic standpoint, pineapple (Ananas comosus) is one of the most important fruits in Colombia. A decade ago, the Perolera variety was the most cropped cultivar of the Santander department, however, the variety has been displaced considerably due to the lack of technical extension services and the introduction of new varieties. This research project was carried out with the intention to conserve the species through the development of in vitro pineapple explants using the organogenesis technique. Meristems that have been extracted from the crown of the Perolera pineapple variety were used for this purpose. Four disinfectant treatments were evaluated by looking at the different kinds of disinfectant exposure times. The treatment that gave the best results in terms of contaminant-free explants was the T2: Commercial detergent + Tween 80 for 8 minutes, ethyl alcohol at 70% for 1 minute and sodium hypochlorite at 1,5% over 10 minutes, with a contamination rate of 7% and 93% of the explants thriving. For the establishment phase, it was found that the medium MS MEP1 with 100% solid salts supplemented with 2000 μl/L BAP - 1000 μl/L ANA - 1000 μl/L AIA and 500 μl/L thiamine enabled 90 % of the pineapple explants to continue developing four weeks after planting. Similarly, the medium containing 3000 μl/L of BAP for the multiplication phase permitted an average proliferation of 4.62 shoots with 9.12 leaves per shoot and a length of 2.25 mm.